Progress in the study of FOXO3a interacting with microRNA to regulate tumourigenesis development - Sun, Liying; Liu, Jiaqi; Bao, Dongbo; Hu, Cheng; Zhao, Yundong; Chen, Shuang (Frontiers in Oncology, 2023)
FOXO3a is a protein of the forkhead box family that inhibits tumour cell growth. One of the regulatory modes affecting the role of FOXO3a is microRNA targeting and degradation of its mRNA expression, and conversely, aberrant expression of FOXO3a as a transcription factor also influences microRNA levels. We summarized the results of the regulatory interactions of twenty-five microRNAs with FOXO3a in five types of malignant tumours and found that dual microRNAs synergize with FOXO3a to inhibit breast cancer cell growth including two groups； Three individual microRNAs collaborated with FOXO3a to restrain hepatocellular carcinoma progression; Twelve individual microRNAs antagonized FOXO3a to promote the development of a single tumour cell, respectively; and five microRNAs antagonized FOXO3a to contribute to the progression of more than two types of tumours. The above findings demonstrated the tumour suppressor effect of FOXO3a, but another result revealed that miR-485-5p and miR-498 inhibited the growth of hepatocellular carcinoma cells by antagonizing FOXO3a when acting in combination with other long -stranded non-coding RNAs, respectively, suggesting that FOXO3a at this moment plays the function of promoting the tumour progression. The PI3K/AKT, Snail, VEGF-NRP1, and Wnt/β-catenin signaling pathways perform crucial roles in the above process. It is anticipated that the above studies will assist in understanding the effects of FOXO3a-MicroRNA interactions in cancer genesis and development, and provide new perspectives in the treatment of malignant tumors.